2016
DOI: 10.1039/c5ce02547h
|View full text |Cite
|
Sign up to set email alerts
|

Growth of hollow-structured LiMn2O4crystals starting from Mn metal in molten KCl through the microscale Kirkendall effect

Abstract: Hollow-structured LiMn 2 O 4 crystals are grown in molten KCl (flux) for the first time via an oxidation reaction of metallic Mn followed by a lithiation reaction. Characterization of the formation process, which is achieved using thermogravimetric differential thermal analysis, X-ray diffraction, and scanning electron microscopy observation, reveals that the hollow structures are formed via a mechanism analogous to the microscale Kirkendall effect, which results from the difference between the solid-state dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…S1). Very similar results were observed in our previous reports that describe the formation of hollow-structured LiCoO 2 , LiMn 2 O 4 , and LiNi 0.5 Co 0.2 Mn 0.3 O 2 from the conversion of electrodeposited Co, Mn, and stacked Ni/Co/Mn dots in molten salts at high temperatures, respectively 23,24 . Based on these results, the oxide formation on the Nb substrate could limit the reaction kinetics, since the amount of dissolved oxygen is normally small in the molten salts.…”
Section: Resultssupporting
confidence: 91%
“…S1). Very similar results were observed in our previous reports that describe the formation of hollow-structured LiCoO 2 , LiMn 2 O 4 , and LiNi 0.5 Co 0.2 Mn 0.3 O 2 from the conversion of electrodeposited Co, Mn, and stacked Ni/Co/Mn dots in molten salts at high temperatures, respectively 23,24 . Based on these results, the oxide formation on the Nb substrate could limit the reaction kinetics, since the amount of dissolved oxygen is normally small in the molten salts.…”
Section: Resultssupporting
confidence: 91%
“…The LiNi 0.5 Mn 1.5 O 4− δ crystals used were prepared by the flux growth method171819202122. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…14,23 It has been reported that the KE can happen between Mn and Fe, Fe and O, and Mn and O, respectively, if there exists enough of a chemical potential gradient. 36,40,41 In our experiment, once the precursor Mn 3 O 4 starts to react with Fe 2+ , Mn 3 O 4 converts into Mn x Fe y O 4 , and there will be a gradient difference in element concentration between the inner and surface layers of nanoparticles. Internal Mn is higher than external Mn, while internal Fe is less than external Fe.…”
mentioning
confidence: 89%
“…In this secondary reaction, the Mn atoms can diffuse out of the solid without the Mn/Fe exchange, which is the typical characterization of the KE. 36 Another possibility for the secondary reaction is the Ostwald ripening. 37−39 However, according to the crystallization condition of large precursor Mn 3 O 4 crystals (Figure S1) and the relative lower reaction temperature, it is reasonable to exclude the Ostwald ripening, and the KE is dominated for the secondary reaction.…”
mentioning
confidence: 99%